Comorbidities frequency in takotsubo syndrome: An international collaborative systematic review including 1109 patients - Francesco Pelliccia (2018)
© 2015 Elsevier Inc. All rights reserved. Background To identify predisposing factors that can result in the onset of takotsubo syndrome, we performed an international, collaborative systematic review focusing on clinical characteristics and comorbidities of patients with takotsubo syndrome. Methods We searched and reviewed cited references up to August 2013 to identify relevant studies. Corresponding authors of selected studies were contacted and asked to provide additional quantitative details. Data from each study were extracted by 2 independent reviewers. The cumulative prevalence of presenting features and comorbidities was assessed. Nineteen studies whose authors sent the requested information were included in the systematic review, with a total of 1109 patients (951 women; mean age, 59-76 years). Evaluation of risk factors showed that obesity was present in 17% of patients (range, 2%-48%), hypertension in 54% (range, 27%-83%), dyslipidemia in 32% (range, 7%-59%), diabetes in 17% (range, 4%-34%), and smoking in 22% (range, 6%-49%). Emotional stressors preceded takotsubo syndrome in 39% of patients and physical stressors in 35%. The most common comorbidities were psychological disorders (24%; range, 0-49%), pulmonary diseases (15%; range, 0-22%), and malignancies (10%; range, 4%-29%). Other common associated disorders were neurologic diseases (7%; range, 0-22%), chronic kidney disease (7%; range, 2%-27%), and thyroid diseases (6%; range, 0-37%). Conclusions Patients with takotsubo syndrome have a relevant prevalence of cardiovascular risk factors and associated comorbidities. Such of associations needs to be evaluated in further studies.